2013
DOI: 10.1016/j.nbd.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Two different interictal spike patterns anticipate ictal activity in vitro

Abstract: Abstract4-Aminopyridine (4AP, 50 μM) induces interictal-and ictal-like discharges in brain slices including parahippocampal areas such as the entorhinal cortex (EC) but the relation between these two types of epileptiform activity remains undifined. Here, by employing field potential recordings in rat EC slices during 4AP application, we found that: (i) interictal events have a wide range of duration (0.4-3.3 s) and interval of occurrence (1.4-84 s); (ii) ictal discharges are either preceded by an isolated "sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
6
20
1
Order By: Relevance
“…We have confirmed here that ionotropic glutamatergic receptor-mediated signaling is required for the generation of ictal discharges in both PC and EC (Avoli et al, 2013;Hamidi et al, 2014;Herrington et al, 2014). In keeping with evidence obtained in these previous studies, we have found that blockade of glutamatergic signaling using NMDA and non-NMDA receptor antagonists led to the occurrence of isolated, slow GABA receptordependent potentials during application of 4AP.…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andsupporting
confidence: 91%
“…We have confirmed here that ionotropic glutamatergic receptor-mediated signaling is required for the generation of ictal discharges in both PC and EC (Avoli et al, 2013;Hamidi et al, 2014;Herrington et al, 2014). In keeping with evidence obtained in these previous studies, we have found that blockade of glutamatergic signaling using NMDA and non-NMDA receptor antagonists led to the occurrence of isolated, slow GABA receptordependent potentials during application of 4AP.…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andsupporting
confidence: 91%
“…Low-voltage fast activity and hypersynchronous onset patterns can also be reproduced in a combined hippocampus-entorhinal cortex, or hippocampus amygdala slices perfused in vitro with either 4AP (Lopantsev and Avoli 1998;Avoli et al 2013b), low-magnesium and highpotassium solution (Derchansky et al 2006;Zhang et al 2012), as well as following highfrequency tetanic stimulation (Isomura et al 2008;Fujiwara-Tsukamoto et al 2010). In these in vitro models, low-voltage fast activity onset is characterized at the start by a prominent activation of inhibitory interneurons (Velazquez and Carlen 1999;Kohling et al 2000;Ziburkus et al 2006;Lasztoczi et al 2009;Fujiwara-Tsukamoto et al 2010), which transiently shut off principal cells ( Fig.…”
Section: Seizure Onsetmentioning
confidence: 88%
“…These two seizure onset types, which are also recorded in animal models both in vitro (Fig. 5C) [76][77][78] and in vivo (Fig. 5D) [42,45], suggest that the spiking dynamics occurring at the onset of a seizure may mirror different pathophysiological mechanisms.…”
Section: Interictal-ictal Interactionsmentioning
confidence: 70%